The Impact of the Implementation of Business Intelligent to Support Decision-Making in the American Banking Industry: A Literature Review - Sundjaja, Arta Moro; Veronica, Veronica (ComTech: Computer, Mathematics and Engineering Applications, 2016)
In facing globalization era, companies need to have innovation to survive in business competition. A change is needed to make a successful inovation, when a company needs a leader who has a strong managerial ability. The application of technology, in this case is business intelligence (BI), is an innovation that can becarried out by the management leader to survive in the complex world competition by finding appropriate decisions to solve business problems. This article was a literature review that concerned to exploration of the role of leadership and managerial ability in the application of BI on First American Company (FAC). The authors retrieved articles from google scholar with keywords, such as: leadership, managerial ability, and business. The implementation of BI on FAC proves to be a successful innovation formulated by the managementwho manage to change the company's financial situation that loss into a profit and managed to become the market leaders. In addition, this article also presented some cases of successful BI implementation which helped resolving credit problems and segmentation